Unveiling the impact of organically activated biochar on physiological, biochemical, and yield attributes of maize under varied field moisture conditions - Iqbal, Hajra; Jahan, Summera; Akbar, Muhammad; Kamran, Atif; Rasul, Fahd; Shahzad, Sobia; Siddiqui, Manzer H.; Alamri, Saud (PeerJ, 2024)
Water deficiency in semiarid regions is a limiting factor that affects crop quality and yield. In Punjab, Pakistan, a 27% decline in maize yield was detected over the past two decades just because of water scarcity. Currently, no studies have reported the effects of organically activated biochar (AB) on crop productivity under natural field conditions. For this purpose, a field experiment in a split-split-plot design was conducted with three amendment levels (0, 2, and 4 tonnes ac−1), and three maize hybrids (DK-9108, DK-6321, and Sarhaab) under 100%, 70%, and 50% irrigation water (IW) of crop evapotranspiration (ETc). The AB significantly improved the soil’s physical and chemical properties, and maximum improvement was recorded in 4 tonnes ac−1 AB amendment in organic matter (16.6%), total organic carbon (17%), phosphorus (11.43%), and available potassium (29.27%). The 4 tonnes ac−1AB amendment in soil had a significant impact on total chlorophyll content (0.3–1-fold in DK-6321), carotenoid content (3.9–4.4-fold in Sarhaab), and relative water content (30% and 21% in Sarhaab) under 50% irrigation water (IW) of ETc at V14th and R3 stages, respectively. Moreover, a significant decline in stress markers (proline content and sugar content) was detected at both growth stages in all maize hybrids in AB amended soil. The analysis of plant metabolites indicated increased intensities of phenolics, alkyl esters, and carbohydrates by 2.5–7%, 17–80%, and 40–43% in DK-6321 under 50% IW in 2–4 tonnes ac−1 AB amended soil, respectively. The highest improvement in growth and yield attributes among maize hybrids was detected in the order DK-6321¿DK-9108¿Sarhaab in 2–4 tonnes ac−1AB amended soil under 70% and 50% IW of ETc, respectively. Hence, this research might help to develop an effective soil amendment to restore degraded soils and improve maize growth under arid climatic conditions.
Keywords: Nutrient composition of soil; Water stress; FTIR analysis of maize metabolites; Photosynthetic pigments; Yield attributes